Corporate Governance, Transparency and Stock Return Synchronicity - Werner Ria Murhadi; Liliana Inggrit Wijaya (Program MM Universitas Surabaya, 2021)
This study aims to analyze the effect of corporate governance on transparency as measured by stock return synchronicity. The variables used are board size (commissioner), big4 audit, institutional ownership, market to book, the volatility of firm fundamentals, leverage, and firm size. This study uses a quantitative approach with multiple linear analysis models. This study uses a sample of non-financial business entities listed on the Indonesia Stock Exchange (BEI). The number of samples used in this study was 198 observations. The results showed that the variable board size (commissioner), institutional ownership, and leverage had a positive effect on transparency, and the implied volatility of the firm hurt transparency. Other variables such as big4 audit, market to book ratio, and firm size do not affect transparency.